Analysis of the Trends and Factors Associated with the Availment of Optional Retirement among PNP Personnel - Ambata, Maria May M.; Bautista, Kyle Gabriel E.; Enoc, Noel B.; Hizon, Irine B.; Pamaos, Kevin E.; Villa, Elizabeth B.; Mobo, Froilan D.; Golla, Nathaniel S. (Future Science / FSH-PH Publications, 2025)
This research study aimed to analyze the emerging trends of option-al retirement among PNP personnel and present the trends in the NHQwhich was the highest number of applicants for early retire-ment. It focused on ascertaining the various contributory factors that lead to the vast increase in PNP personnel acquiring early re-tirement. This study also determined the major or common causes why PNP personnel opted to avail of the optional retirement rather than rendering the full length of service.It led to the specification of causal factors including personal reasons, workplace conditions, broader organizational issues, and others. This reflected the com-plex relationship of personal and organizational dynamics that in-fluence retirement decisions within the PNP organization.This study employed a descriptive method of investigation, utilizing stratified random sampling to select the thirty-six (36) respondents. The in-formation gathered from the group of participants from the records at the PRBS conducted at the National Headquarters (NHQ) of the Philippine National Police situated in Camp Rafael T. Crame, Quezon City. From 2019 to 2024 applicants submitted requests for optional retirement benefits. The findings led the PNP organization to pro-pose recommendedpolicy enhancementby the respondents which may be forwarded to the Administrative and Resource Management Division to retain the remaining personnel and maintain morale, such as providing incentives or professional growth opportunities. The management may also strategize on the effective promotion of the organization to encourage more qualified candidates to apply and sustain the ideal workforce balance within the police organiza-tion.